Unstoppable : the incredible power of faith in action - Vujicic, Nick. (Colorado Springs, Colorado : Waterbrook Press, 2013)
Reveals how the author learned to deal with adverse circumstances in such areas as relationships, careers, health, and bullying through the experiences he has endured having been born without arms or legs.
Keywords: Faith; Encouragement -- Religious aspects -- Christianity; Inspiration -- Religious aspects -- Christianity; Success -- Religious aspects -- Christianity; Abnormalities, Human -- Biography